2023
DOI: 10.3390/plants12040937
|View full text |Cite
|
Sign up to set email alerts
|

Persimmon Leaves: Nutritional, Pharmaceutical, and Industrial Potential—A Review

Abstract: Persimmon is a delicious fruit, and its leaves are considered a valuable ingredient in food, beverage, pharmaceutical, and cosmetic sectors. Traditionally, persimmon leaves (PL) are used as a functional tea in Asian culture to cure different ailments, and are also incorporated into various food and cosmeceutical products as a functional ingredient. PL mainly contain flavonoids, terpenoids, and polysaccharides, along with other constituents such as carotenoids, organic acids, chlorophylls, vitamin C, and minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Persimmon is an East Asian fruit that is renowned for its nutritional value due to its high content of antioxidant compounds, especially flavonoids. Previous studies have confirmed that persimmon leaves contain a wide range of bioactive compounds such as flavonoids, terpenoids, polysaccharides, caffeine, carotenoids, amino acids, vitamin C, minerals, and chlorophylls 4 . PLE, in particular, is high in phenolic compounds such as proanthocyanidins, quercetin, catechin, and flavonoids, which may contribute to its antioxidant and anti‐inflammatory effects.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Persimmon is an East Asian fruit that is renowned for its nutritional value due to its high content of antioxidant compounds, especially flavonoids. Previous studies have confirmed that persimmon leaves contain a wide range of bioactive compounds such as flavonoids, terpenoids, polysaccharides, caffeine, carotenoids, amino acids, vitamin C, minerals, and chlorophylls 4 . PLE, in particular, is high in phenolic compounds such as proanthocyanidins, quercetin, catechin, and flavonoids, which may contribute to its antioxidant and anti‐inflammatory effects.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have confirmed that persimmon leaves contain a wide range of bioactive compounds such as flavonoids, terpenoids, polysaccharides, caffeine, carotenoids, amino acids, vitamin C, minerals, and chlorophylls. 4 PLE, in particular, is high in phenolic compounds such as proanthocyanidins, quercetin, catechin, and flavonoids, which may contribute to its antioxidant and anti‐inflammatory effects. Since hair growth and aging are influenced not only by genetic and chronological factors, but also by environmental factors such as solar radiation and air pollution, the effects of PLE can result in the long‐term preservation of hair health in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diospyros kaki Thunb., also referred to as persimmon, is an important fruit in China and a representative species for economic exploitation. The traditional main producers of persimmons are China, Korea, and Japan [1]. China was the first country to cultivate persimmon trees, and the common use of persimmon fruits was recorded as early as the Han dynasty [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is also grown in India, Azerbaijan, Spain, Turkey, Brazil, and the United States. Although persimmon fruit is consumed fresh or dried, tea is made from its leaves in East Asian countries (Hossain & Shahidi, 2023). It is seen that the flesh or pulp of fresh, fully ripe fruits can be used widely, whereas other parts, such as peel, calyx, and seed, are discarded (Lee et al., 2023).…”
Section: Introductionmentioning
confidence: 99%